Developments of Picosecond Lasers Based on Stimulated Brillouin Scattering Pulse Compression - Cao, Chen; Wang, Yulei; Bai, Zhenxu; Li, Yunfei; Yu, Yu; Lu, Zhiwei (Frontiers in Physics, 2021)
With high efficiency and narrow output width, pulse compression based on stimulated Brillouin scattering (SBS) is a nonlinear optical approach that efficiently converts high-energy nanosecond pulses into the picosecond. Since the first observation of SBS pulse compression, different compression structures for different input and output parameters were developed to optimize the characteristics of pulse compression in the past decades. Here, a comprehensive review of the development status of SBS pulse compression schemes is provided, meanwhile, methods and trends to the optimization of SBS pulse compression are proposed.